Biomass-Derived Porous Carbon Materials for Supercapacitor - Yang, Hui; Ye, Shewen; Zhou, Jiaming; Liang, Tongxiang (Frontiers in Chemistry, 2019)
The fast consumption of fossil energy accompanied by the ever-worsening environment urge the development of clean energy and novel energy storage system. As one of the most promising candidates, supercapacitor owns unique advantages, and numerous electrodes materials have been exploited. Hence, biomass-derived porous carbon materials (BDPCs), with low cost, abundant, sustainable, adjustable dimension, superb electrical conductivity, satisfactory specific surface area (SSA) and superior electrochemical stability, have been attracted intense attention and highly trusted to be a capable candidate for supercapacitors. This review will highlight the recent lab-scale methods for preparing BDPCs, and analyze their effects on BDPCs' microstructure, electrical conductivity, chemical composition and electrochemical properties. Future research trends in this field also will be provided.